Transcultural adaptation and validation of the Celiac Disease Quality of Life (CD-QOL) survey, a specific questionnaire to measure quality of life in patients with celiac disease - Francesc Casellas; Luis Rodrigo; Javier Molina-Infante; Santiago Vivas; Alfredo J. Lucendo; Mercé Rosinach; Carmen Dueñas; Fernando Fernández-Bañares; Josefa López-Vivancos (Revista Espanola de Enfermedades Digestivas, 2013)
Introduction: celiac disease is a chronic condition that requires continued treatment, with the resultant impact on health-related quality of life (HRQOL) of people who suffer it. Most studies in this field have used generic questionnaires to measure HRQOL in celiac patients. It was therefore decided to conduct a study to translate into Spanish and validate a specific questionnaire for celiac disease, the Celiac Disease Quality Of Life Survey (CD-QOL). Objectives: to translate and validate in Spanish the specific celiac disease questionnaire CD-QOL. Methods: a multicenter, prospective, observational study was designed consisting of two phases: In the first phase, the questionnaire was translated and adapted into Spanish using the translation/back translation procedure and an understandability study. In the second phase, internal consistency of the translated questionnaire was analyzed. For this, results of the CD-QOL were compared to those of EuroQol and the Daily Fatigue Impact Scale (D-FIS). Understandability of the translated and adapted questionnaire was tested in six patients, and the validation study was done in 298 celiac patients (201 treated with a gluten-free diet and 97 at diagnosis). Results: in both celiac groups, Cronbach's alpha coefficient was high (0.90), feasibility was excellent (99.2 % of patients completed all questions), and there were no ceiling and floor effects. Spearman correlation to EuroQol and D-FIS was statistically significant (p < 0.05). CD-QOL score was different depending on whether state of health was good, fair, or poor based on the EuroQol score. Conclusion: the Spanish version of the CD-QOL is a valid tool for measuring HRQOL in celiac patients.